2014
DOI: 10.1007/s00432-014-1713-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative transcatheter arterial chemoembolization on gene expression in the HIF-1α pathway in patients with hepatocellular carcinoma

Abstract: Our findings collectively demonstrate that preoperative TACE confers poor prognosis in HCC patients through activation of HIF-1α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…We focused on the pharmacokinetics of sorafenib during the period within 72 hours after transarterial chemoembolization. Transarterial chemoembolization induces immediate hypoxia of the HCC cells and can upregulate angiogenesis (3,4). A clinical study of combined transarterial chemoembolization and oral administration of sorafenib investigated the possibility that "rebound" may result from 3-4 days of sorafenib interruption, before and after transarterial chemoembolization (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the pharmacokinetics of sorafenib during the period within 72 hours after transarterial chemoembolization. Transarterial chemoembolization induces immediate hypoxia of the HCC cells and can upregulate angiogenesis (3,4). A clinical study of combined transarterial chemoembolization and oral administration of sorafenib investigated the possibility that "rebound" may result from 3-4 days of sorafenib interruption, before and after transarterial chemoembolization (17).…”
Section: Discussionmentioning
confidence: 99%
“…If transarterial chemoembolization does not induce complete necrosis of the tumor, the residual surviving cancerous tissue overexpresses vascular endothelial growth factor (VEGF) (3). A more recent study revealed that preoperative transarterial chemoembolization confers a poor prognosis in patients with HCC through activation of hypoxia-inducible factor 1α (HIF-1α) (4). Thus, inhibition of angiogenesis is critical for successful treatment of HCC.…”
mentioning
confidence: 98%
“…It is worried that if tumors cannot achieve complete pathological response after chemoembolization, the residual intrahepatic tumor cells may develop resistance toward chemotherapeutic agents and become more invasive than those receiving no TACE treatment. [27,28] The intratumoral necrosis induced by TACE may weaken the adhesive potential of the tumor and subsequently facilitate the release of cancer cells from the primary tumor and dislodgment into the bloodstream, thus increasing the risk of postoperative recurrence. [29] Our study showed that: for patients from mean tumor diameter >5 cm subgroup, the complete necrosis rate was all below 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a combination with HAC or HAC alone was superior to other methods in advanced stages (C, D). This finding may be related to the metabolism of tumors in the hypoxic environment [2021]. Based on these results, it is possible to conclude that LT (if possible) was the best option for patients at Stage 0, whereas TACE+RFA, SR, PEI might be potential best options for patients at Stage 0 (if LT is not possible).…”
Section: Discussionmentioning
confidence: 94%